Glacier variations and rising temperature in the Mt. Kenya since the Last Glacial Maximum - Chen, AA; Wang, NL; Guo, ZM; Wu, YW; Wu, HB (Journal of Mountain Science, 2018)
High-resolution imagery can be used to reconstruct former glacier boundaries through the identification of glacial erosional and sedimentary geomorphology. We employed moraine mapping and the accumulation-area ratio method (AAR), in conjunction with Landsat, Google Earth, and SRTM imagery, to reconstruct glacier boundaries and equilibrium-line altitudes (ELAs) for Mt. Kenya in the Last Glacial Maximum (LGM), the Little Ice Age (LIA), and at present. Our results show that the areas of Lewis Glacier and the Tyndall-I glacier system were 0.678 km(2) and 0.390 km(2), respectively, during the maximum of LIA. Those mean that the both glaciers have shrunken by 87.0% and 88.7%, respectively since the LIA. Area change ratios for each glacier were significantly larger in the period of 2000 through 2015 than the former periods, indicating that glacier recession has accelerated. Continuous ice loss in this region has been driven by rising temperature and fluctuating precipitation. Linear regression data for Lewis glacier show that mass balance sensitivity to dry season temperature was-315 mm w.e./A degrees C, whereas the sensitivity to dry season precipitation was 5.2 mm w.e./mm. Our data also show that the ELA on the western slope of Mt. Kenya rose by 716-816 m from the LGM to the modern era, corresponding to that temperature rose by 5.2A degrees C -6.5A degrees C.